2017
DOI: 10.1038/srep39868
|View full text |Cite
|
Sign up to set email alerts
|

Membrane translocation of t-SNARE protein syntaxin-4 abrogates ground-state pluripotency in mouse embryonic stem cells

Abstract: Embryonic stem (ES) and induced pluripotent stem (iPS) cells are attractive tools for regenerative medicine therapies. However, aberrant cell populations that display flattened morphology and lose ground-state pluripotency often appear spontaneously, unless glycogen synthase kinase 3β (GSK3β) and mitogen-activated protein kinase kinase (MEK1/2) are inactivated. Here, we show that membrane translocation of the t-SNARE protein syntaxin-4 possibly is involved in this phenomenon. We found that mouse ES cells cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 61 publications
2
9
0
Order By: Relevance
“…signaling with retaining the ability to activate TGF-b, to realize the marked posttranscriptional upregulation of aSMA. Alternative possibility is that, GSK3 kinases, a possible signaling element of extracellular subpopulations of plasmalemmal syntaxin [51], could be involved in the posttranscriptional regulation of aSMA, given their role in the activation of eEF2 kinase [49].…”
Section: Discussionmentioning
confidence: 99%
“…signaling with retaining the ability to activate TGF-b, to realize the marked posttranscriptional upregulation of aSMA. Alternative possibility is that, GSK3 kinases, a possible signaling element of extracellular subpopulations of plasmalemmal syntaxin [51], could be involved in the posttranscriptional regulation of aSMA, given their role in the activation of eEF2 kinase [49].…”
Section: Discussionmentioning
confidence: 99%
“…In other cell systems, such as embryonic stem (ES) and embryonic carcinoma (EC) cells, syntaxin-4 post-transcriptionally downregulated E-cadherin expression and transcriptionally upregulate P-cadherin expression, both of which appear to be key events for the induction of EMT phenotypic features. 40 In these embryonic cells, P-cadherin should exert functions not related to intercellular connection. 41,42 P-cadherin presumably acts in FIGURE 8 Epithelial heterogeneity created by local extrusion of syntaxin-4 might be an important component for generation of asymmetric epithelial morphogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to this, we detected a firm association of syntaxin‐4 with P‐cadherin, another class of intercellular adhesion molecule. In other cell systems, such as embryonic stem (ES) and embryonic carcinoma (EC) cells, syntaxin‐4 post‐transcriptionally downregulated E‐cadherin expression and transcriptionally upregulate P‐cadherin expression, both of which appear to be key events for the induction of EMT phenotypic features . In these embryonic cells, P‐cadherin should exert functions not related to intercellular connection .…”
Section: Discussionmentioning
confidence: 99%
“…We also found that these cells decreased E-cadherin expression and are prone to differentiation into mesodermal lineages. Transcriptome analyses revealed that extracellular extrusion of syntaxin4 occurs concomitantly with steep upregulation of P-cadherin, a classical cadherin (Hagiwara-Chatani et al 2017). During early embryogenesis, the expression of P-cadherin protein reportedly substitutes for that of E-cadherin around the primitive streak upon gastrulation and becomes detectable in emerging mesoderm (Acloque et al 2017;Moly et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While either naïve or prime state ES cells express E-cadherin for selective cell-cell adhesion, Pcadherin is normally undetectable in these pluripotent cells (Hagiwara-Chatani et al 2017). The homophilic interaction between the characteristic extracellular domain in each cadherin determines the cell-clustering specificity; however, all classical cadherins share binding partners for linkage to the cytoskeletal actin network (Green et al 2020;Kang et al 2017).…”
mentioning
confidence: 99%